Late Probing for Congenital Nasolacrimal Duct Obstruction - Abrishami, Mohammad (Ophthalmic Research Center, 2009)
PURPOSE: To report the results of late nasolacrimal duct probing in patients with congenital nasolacrimal duct obstruction (NLDO). METHODS: This retrospective study was performed on a consecutive series of patients with congenital NLDO who underwent late (after 15 months of age) nasolacrimal duct probing for the first time. RESULTS: Over a period of five years, 158 patients including 75 (47.4%) male and 83 (52.6%) female subjects with mean age of 3±4.2 years (range, 15 months to 37 years) underwent initial probing for NLDO. Nasolacrimal duct probing was performed unilaterally in 78% and bilaterally in 22% of the patients. Success rate was 75% overall, 72% in unilateral cases and 83% in bilateral instances. Success rate was not correlated with age at intervention. CONCLUSION: Nasolacrimal duct probing seems to be reasonably successful for treatment of congenital NLDO in patients older than 15 months who are seen for the first time. Silicone intubation or dacryocystorhinostomy should be reserved for refractory cases.